2017
DOI: 10.20960/nh.519
|View full text |Cite
|
Sign up to set email alerts
|

Oral glutamine reduces myocardial damage after coronary revascularization under cardiopulmonary bypass. A randomized clinical trial

Abstract: Preoperative oral glutamine standardized at a dose of 0.5 g/kg/day in our study group showed a significant reduction in postoperative myocardial damage. Lower cardiac injury markers levels, morbidity and mortality were observed in patients receiving glutamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…In addition, a genome-wide association study identified a genetic variant associated with diminished GS expression, which may lead to a Gln deficiency, to the development of coronary artery disease in type 2 diabetes [42]. Interestingly, small clinical trials indicate that Gln supplementation enhances myocardial repair in patients with coronary artery disease and limits cardiac damage after coronary revascularization [43,44,45]. Moreover, a prospective study in two large, well-defined and independent cohorts showed that dietary intake of Gln and the plasma Gln:Glu ratio were inversely related to the risk of cardiovascular mortality, independent of other dietary or lifestyle factors [46].…”
Section: L-glutamine and Cardiometabolic Diseasementioning
confidence: 99%
“…In addition, a genome-wide association study identified a genetic variant associated with diminished GS expression, which may lead to a Gln deficiency, to the development of coronary artery disease in type 2 diabetes [42]. Interestingly, small clinical trials indicate that Gln supplementation enhances myocardial repair in patients with coronary artery disease and limits cardiac damage after coronary revascularization [43,44,45]. Moreover, a prospective study in two large, well-defined and independent cohorts showed that dietary intake of Gln and the plasma Gln:Glu ratio were inversely related to the risk of cardiovascular mortality, independent of other dietary or lifestyle factors [46].…”
Section: L-glutamine and Cardiometabolic Diseasementioning
confidence: 99%
“…Chavez-Tostado et al também demonstraram menor morbidade, menor uso de medicamento vasoativo, menor incidência de infarto agudo do miocárdio, menor taxa de infecção, menor hemorragia e menor necessidade de nova intervenção cirúrgica no grupo que recebeu a intervenção estudada. 15,25 Ao se comparar estes últimos achados com a literatura atual, vemos que o uso de glutamina já é bem documentado como substrato para síntese de DNA, ATP (molécula de adenosina trifosfato) e proteínas, sendo importante para proliferação vascular, migração e apoptose cardíaca. Desta maneira, é eficaz para diminuir injúria após infarto agudo do miocárdio ou após parada cardiorrespiratória.…”
Section: Discussionunclassified
“…For mice on a high-fat diet, studies show that glutamine intake helps lower body weight, decreases hyperglycemia, and improves insulin sensitivity [57]. In patients with coronary artery diseases, glutamine supplementation enhances myocardial repair and prevents damage to the cardiovascular system during surgical interventions or cardiac injuries [9,58,59]. The protective role of glutamine in ischemia-reperfusion injury is especially well investigated [60][61][62][63][64].…”
Section: Glutamine Supplementation Is Implemented For Treatment Of Cancer and A Variety Of Cardiovascular Diseasesmentioning
confidence: 99%
“…As the fight against these fatal diseases continues, it is crucial that we continue our investigation and broaden our understanding of cancer and cardiovascular diseases to innovate our prognostic and treatment approaches. Even though cardiovascular diseases and cancer are usually studied independently [2][3][4][5][6][7][8][9][10][11][12], there are some striking overlaps between their metabolic behaviors and therapeutic targets, suggesting the potential application of cardiovascular disease treatments for cancer therapy. More specifically, both cancer and many cardiovascular diseases have an upregulated glutaminolysis pathway, resulting in low glutamine and high glutamate circulating levels.…”
Section: Introductionmentioning
confidence: 99%